Heavy metal curing agent and method for curing heavy metal in coal gangue

By using curing agents prepared by materials such as silt, fly ash, bentonite, quartz sand, calcium carbonate and chitosan, the problem of poor curing agents in the prior art is solved, and efficient heavy metal curing and pressure resistance are achieved Increased intensity and reduced environmental pollution.

CN119285284APending Publication Date: 2025-01-10SHENHUA SHENDONG COAL GRP +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411425262.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, the curing agent has poor long-term curing effect on heavy metals and the compressive strength of the cured body formed therein is poor, making it difficult to effectively prevent the heavy metal from spreading outward, resulting in environmental pollution.

Method used

A heavy metal curing agent, including silt, fly ash, bentonite, quartz sand, calcium carbonate and chitosan, is used to prepare blends and silane compounds through calcining, hydroxylation, crosslinking and other steps to form high resistance. The cured body with compressive strength works synergistically to improve the curing effect.

Benefits of technology

It significantly improves the long-term curing effect of heavy metals and the compressive strength of the cured body, reduces the leaching and dissolution of heavy metals, realizes effective curing of heavy metals in coal gangue, and reduces the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081966460000111
    Figure BDA0005081966460000111
  • Figure BDA0005081966460000112
    Figure BDA0005081966460000112
  • Figure BDA0005081966460000121
    Figure BDA0005081966460000121
Patent Text Reader

Abstract

The invention discloses a heavy metal curing agent and a curing method of heavy metals in coal gangue, and relates to the field of heavy metal pollution treatment. The heavy metal curing agent comprises a first curing agent, a second curing agent and a third curing agent; wherein the first curing agent comprises silt, fly ash and bentonite, the second curing agent comprises a blend and chitosan loaded on the surface of the blend, the blend comprises quartz sand and calcium carbonate, and the third curing agent comprises a silane compound. The curing agent has an excellent long-term curing effect on heavy metals, and a cured body formed by the curing agent has excellent compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of heavy metal pollution treatment, and in particular to a heavy metal solidifying agent and a method for solidifying heavy metals in coal gangue. Background Art

[0002] If solid waste (such as coal gangue) is not properly handled, the heavy metals in it will cause certain pollution and impact on the environment. At present, the main way to deal with solid waste is landfill, that is, to bury solid waste in a designated site, but this method may cause pollution to groundwater and soil. Therefore, it is necessary to solidify the heavy metals in solid waste to prevent the heavy metals from spreading outward, thereby achieving harmless treatment of solid waste.

[0003] At present, solidification treatments include cement solidification, lime solidification, thermoplastic / thermosetting solidification and chemical agent solidification. Among them, cement solidification is to use cement to wrap and solidify solid waste after hydration and condensation to form a solidified body in order to control the migration, diffusion and dissolution of heavy metal elements. However, the single cement solidification effect is poor. Lime solidification is to use quicklime or slaked lime as a curing agent to mix and stir solid waste, water and admixtures to form a solidified body, thereby achieving solidification. Although lime has a certain curing effect on heavy metal elements, the long-term curing effect is poor and heavy metals are easy to leach. Thermoplastic material curing is to use thermoplastic materials such as polyolefins, polyether polyesters, paraffin, asphalt as curing agents, so that they soften under high temperature conditions and harden when cooled at low temperature, thereby achieving encapsulation curing. The solidified body obtained by this method has low porosity and poor compressive strength. Due to high temperature operation, a large amount of waste gas will be generated, and the requirements for curing equipment and maintenance costs are high, the cost is high and the impact on the environment is large; chemical agent curing is to use chemical agents to react with heavy metal ions to transform them from a free state to a stable chemical state, and solid waste can be landfilled in the later stage, but the use of chemical agents is prone to environmental pollution and the long-term curing effect is poor. Therefore, how to improve the long-term curing effect of curing agents on heavy metals and the compressive strength of the solidified body formed by them is a technical problem that needs to be solved in this field. Summary of the invention

[0004] The main purpose of the present invention is to provide a heavy metal curing agent and a method for curing heavy metals in coal gangue, so as to solve the problems in the prior art that the curing agent has poor long-term curing effect on heavy metals and the compressive strength of the cured body formed thereby is poor.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a heavy metal curing agent, which includes: a first curing agent, a second curing agent and a third curing agent; wherein the first curing agent includes silt, fly ash and bentonite, the second curing agent includes a blend and chitosan loaded on the surface of the blend, the blend includes quartz sand and calcium carbonate, and the third curing agent includes a silane compound.

[0006] Furthermore, the heavy metal curing agent comprises, by weight: 60-80 parts of a first curing agent, 10-20 parts of a second curing agent and 100-150 parts of a third curing agent; and / or, the first curing agent comprises: 60-100 parts of silt, 10-30 parts of fly ash and 20-40 parts of bentonite.

[0007] Furthermore, in the second curing agent, the mass ratio of the blend to chitosan is 1:(0.5-2.5), and the mass ratio of quartz sand to calcium carbonate is 1:(0.5-1).

[0008] Furthermore, the preparation method of the second curing agent comprises the following steps:

[0009] S1, mixing quartz sand and calcium carbonate, and calcining them under an inert atmosphere to obtain a blend;

[0010] S2, mixing the blend with an alkaline solution, and performing a first thermal stirring to hydroxylate the surface of the blend to obtain an intermediate product;

[0011] S3, mixing chitosan with an acid solution to obtain a solution containing chitosan; mixing the solution containing chitosan, anionic monomer and initiator, and performing a second hot stirring to obtain a mixed solution; adding an intermediate product and a crosslinking agent to the mixed solution, and performing a third stirring to obtain a second curing agent.

[0012] Further, the calcination temperature is 200-400° C. and the calcination time is 1-2 hours; and / or,

[0013] The first thermal stirring temperature is 100-150°C, the rotation speed is 200-400 rpm, and the time is 2-8 hours; and / or,

[0014] The second hot stirring temperature is 60-80°C, the rotation speed is 200-400 rpm, and the time is 1-3 hours; and / or,

[0015] The third stirring temperature is 20-30° C., the rotation speed is 200-400 rpm, and the time is 2-4 hours; and / or,

[0016] After the first heat stirring, the first heat stirring product is subjected to a first washing and a first drying to obtain an intermediate product; and / or,

[0017] After the third stirring, the third stirring product is subjected to a second washing, a second drying, and a pulverization, and a 200-400 mesh sieve to obtain a second curing agent; and / or,

[0018] The mass content of the alkaline compound in the alkaline solution is 2% to 10%, and the mass content of the acidic compound in the acid solution is 3% to 5%;

[0019] Preferably, the alkaline compound includes at least one of sodium hydroxide, sodium carbonate and urea;

[0020] Preferably, the acidic compound includes at least one of hydrochloric acid, nitric acid and sulfuric acid.

[0021] Further, the mass ratio of quartz sand to calcium carbonate is 1:(0.5-1); and / or,

[0022] The mass ratio of the intermediate product to chitosan is 1:(1-2); and / or,

[0023] The mass ratio of anionic monomer to chitosan is (1-3):1; and / or,

[0024] The amount of the initiator added is 0.3% to 0.5% of the mass of the anionic monomer; and / or,

[0025] The amount of crosslinking agent added is 0.1% to 0.3% of the mass of the anionic monomer;

[0026] Preferably, the anionic monomer includes at least one of vinyl sulfonic acid, allyl sulfonic acid, 2-acrylamide-1-methylpropane sulfonic acid, 2-acrylamide-2-methylpropane sulfonic acid, and 2-methacrylamide-2-methylpropane sulfonic acid;

[0027] Preferably, the initiator includes at least one of potassium persulfate, ammonium persulfate, and azobisisobutyronitrile;

[0028] Preferably, the cross-linking agent includes at least one of dicumyl peroxide and benzoyl peroxide.

[0029] Furthermore, the third curing agent is a solution containing a silane compound, and the mass content of the silane compound in the solution containing the silane compound is 0.5% to 1%.

[0030] Further, the silane compound includes a bifunctional silane compound;

[0031] Preferably, the silane compound includes at least one of 1,2-bis(trimethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethane, 1,6-bis(trimethoxysilyl)hexane, 1,6-bis(triethoxysilyl)hexane, 1,8-bis(trimethoxysilyl)octane and 1,8-bis(triethoxysilyl)octane;

[0032] More preferably, the silane compound includes at least one of 1,2-bis(trimethoxysilyl)ethane and 1,2-bis(triethoxysilyl)ethane.

[0033] The second aspect of the present invention provides a method for solidifying heavy metals in coal gangue, the solidification method comprising: mixing coal gangue with a solidifying agent to form a solidified body; curing the solidified body to solidify the heavy metals in the coal gangue; wherein the solidifying agent is the heavy metal solidifying agent provided in the first aspect.

[0034] Furthermore, the mass ratio of coal gangue to heavy metal solidifying agent is (1-3):1; and / or,

[0035] The curing temperature is 15-35℃, the humidity is above 80%, and the curing time is 7-112 days;

[0036] Preferably, the curing temperature is 20-30° C., the humidity is 90%, and the curing time is 7-56 days.

[0037] The technical solution of the present invention is applied to utilize the synergistic effect between the first curing agent, the second curing agent and the third curing agent, wherein the first curing agent can produce a physical wrapping effect on the heavy metal ions after hydration, effectively inhibiting the leaching of heavy metal ions, the surface of the second curing agent has abundant negative charges, which can achieve effective combination with heavy metals, thereby playing a curing role, and the third curing agent can make the first curing agent and the second curing agent tightly adhere to the surface of the solid waste to achieve effective curing. Under the joint action of the three, the long-term curing effect of the curing agent on heavy metals and the compressive strength of the solidified body formed by the curing agent are effectively improved. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0039] As described in the background of the present invention, the curing agent in the prior art has a poor long-term curing effect on heavy metals and the compressive strength of the solidified body formed by the curing agent is poor. In order to solve the above problems, the first aspect of the present invention provides a heavy metal curing agent, the heavy metal curing agent includes: a first curing agent, a second curing agent and a third curing agent; wherein the first curing agent includes silt, fly ash and bentonite, the second curing agent includes a blend and chitosan loaded on the surface of the blend, the blend includes quartz sand and calcium carbonate, and the third curing agent includes a silane compound.

[0040] The heavy metal solidifying agent of the present invention can be directly mixed with solid waste and water to form a solidified body to achieve the solidification of coal gangue. The solid waste can be, for example, coal gangue, and the heavy metal solidifying agent can also be applied to other solid wastes, which is not limited in the present invention.

[0041] Among them, silt has lower permeability and higher plasticity. Fly ash is a byproduct produced during the combustion process of coal-fired power plants. It is mainly composed of fine particles formed by the combustion of minerals in coal at high temperatures. It can improve physical adsorption performance and reduce costs. Bentonite is a natural clay mineral, mainly composed of montmorillonite minerals. Bentonite has high expansibility and adsorption, and its volume can increase significantly when in contact with water. By introducing a first curing agent including silt, fly ash and bentonite, these three can produce a physical wrapping effect on heavy metal ions after hydration, effectively inhibiting the leaching of heavy metal ions.

[0042] In the second curing agent, the blend can be a mixture of quartz sand and calcium carbonate. The main component of quartz sand is silicon dioxide. The blend formed by the two has high hardness, strong acid resistance and good thermal stability. Quartz sand and calcium carbonate are both natural minerals, and the impact of mining and use on the environment is relatively small. Chitosan is loaded on the surface of the blend. Under the joint action of the blend and chitosan, the surface of the second curing agent has abundant negative charges, which can achieve effective combination with heavy metal ions, thereby playing a curing role.

[0043] The present invention utilizes the synergistic effect between the first curing agent, the second curing agent and the third curing agent. After being hydrated, the first curing agent can produce a physical wrapping effect on the heavy metal ions, effectively inhibiting the leaching of the heavy metal ions; the surface of the second curing agent has abundant negative charges, which can achieve effective combination with the heavy metals, thereby playing a curing role; the third curing agent can make the first curing agent and the second curing agent tightly adhere to the surface of the solid waste, achieving effective curing. Under the joint action of the three, the long-term curing effect of the curing agent on the heavy metals and the compressive strength of the solidified body formed thereby are effectively improved.

[0044] In some embodiments, the heavy metal curing agent includes, by weight, 60 to 80 parts of a first curing agent, 10 to 20 parts of a second curing agent, and 100 to 150 parts of a third curing agent. By further limiting the weight of the first curing agent, the second curing agent, and the third curing agent, the long-term curing effect of the curing agent on the heavy metal and the compressive strength of the cured body formed by the curing agent can be further improved.

[0045] In some embodiments, the first curing agent includes, by weight, 60-100 parts of silt, 10-30 parts of fly ash, and 20-40 parts of bentonite. By limiting the weight of each component in the first curing agent, the long-term curing effect of the curing agent and the compressive strength of the cured body formed by the curing agent can be further improved.

[0046] In some embodiments, in the second curing agent, the mass ratio of the blend to chitosan is 1:(0.5-2.5), for example, 1:0.5, 1:1, 1:2, 1:2.5 or a range consisting of any two thereof; the mass ratio of quartz sand to calcium carbonate is 1:(0.5-1), for example, 1:0.5, 1:0.8, 1:1 or a range consisting of any two thereof. By limiting the mass ratio of each component in the second curing agent, the number of negative charges on the surface of the second curing agent can be maximized, heavy metal ions can be effectively captured, and long-term effective curing can be achieved.

[0047] In some embodiments, the preparation method of the second curing agent comprises the following steps:

[0048] S1, mixing quartz sand and calcium carbonate, and calcining them under an inert atmosphere to obtain a blend;

[0049] S2, mixing the blend with an alkaline solution, and performing a first thermal stirring to hydroxylate the surface of the blend to obtain an intermediate product;

[0050] S3, mixing chitosan with an acid solution to obtain a solution containing chitosan; mixing the solution containing chitosan, anionic monomer and initiator, and performing a second hot stirring to obtain a mixed solution; adding an intermediate product and a crosslinking agent to the mixed solution, and performing a third stirring to obtain a second curing agent.

[0051] Specifically, S1 is essentially to promote the formation of a blend of quartz sand and calcium carbonate, S2 is essentially to hydroxylate the surface of the blend so that chitosan can be subsequently loaded on the surface, and in S3, chitosan is first polymerized with anionic monomers under the action of an initiator to form an anionic monomer-grafted chitosan copolymer, which is then cross-linked with the surface hydroxylated blend to load (or encapsulate) chitosan on the surface of the copolymer, thereby finally obtaining a second curing agent.

[0052] The present invention does not limit the condition parameters in the preparation process. In some embodiments, the calcination temperature is 200-400°C, such as 200°C, 300°C, 400°C or a range consisting of any two thereof, and the time is 1-2h, such as 1h, 1.5h, 2h or a range consisting of any two thereof. In S2, during the first hot stirring process, the surface of the blend is hydroxylated under the action of an alkaline solution to obtain a surface hydroxylated copolymer, i.e., an intermediate product. In some embodiments, the temperature of the first hot stirring is 100-150°C, such as 100°C, 120°C, 150°C or a range consisting of any two thereof, the rotation speed is 200-400rpm, and the time is 2-8h. In S3, during the second hot stirring process, chitosan and anionic monomers undergo polymerization reaction under the action of an initiator to form an anionic monomer grafted chitosan copolymer, and the mixed solution contains an anionic monomer grafted chitosan copolymer. In some embodiments, the temperature of the second hot stirring is 60 to 80°C, for example, 60°C, 70°C, 80°C or any two thereof, the speed is 200 to 400 rpm, and the time is 1 to 3 hours. During the third stirring process, the anionic monomer grafted chitosan copolymer in the mixed solution is cross-linked with the intermediate product under the action of a cross-linking agent, so that the chitosan is loaded on the surface of the blend. In some embodiments, the temperature of the third stirring is 20 to 30°C, for example, 20°C, 25°C, 30°C or any two thereof, the speed is 200 to 400 rpm, and the time is 2 to 4 hours.

[0053] In order to further purify the reaction product, in some embodiments, after the first hot stirring, the first hot stirring product is subjected to a first washing and a first drying to obtain an intermediate product for removing unreacted raw materials and solution. In some embodiments, after the third stirring, the third stirring product is subjected to a second washing, a second drying, and a crushing, and a 200-400 mesh sieve is passed to obtain a second curing agent.

[0054] The present invention does not limit the specific composition and concentration of the raw materials, and can be adjusted according to actual needs. In some embodiments, the mass content of the alkaline compound in the alkaline solution is 2% to 10%, such as 2%, 5%, 8%, 10% or a range consisting of any two thereof. The mass content of the acidic compound in the acid solution is 3% to 5%, such as 3%, 4%, 5% or a range consisting of any two thereof. Among them, the alkaline compound can include at least one of sodium hydroxide, sodium carbonate, and urea, and the acidic compound can include at least one of hydrochloric acid, nitric acid, and sulfuric acid.

[0055] The present invention does not limit the specific addition amount of each raw material, and can be adjusted according to actual needs. For example, in some embodiments, the mass ratio of quartz sand to calcium carbonate is 1: (0.5-1), such as 1: 0.5, 1: 0.8, 1: 1 or a range consisting of any two of them. The mass ratio of the intermediate product to chitosan is 1: (1-2), such as 1: 1, 1: 1.5, 1: 2 or a range consisting of any two of them. The mass ratio of the anionic monomer to chitosan is (1-3): 1, such as 1: 1, 2: 1, 3: 1 or a range consisting of any two of them. The amount of the initiator added is 0.3% to 0.5% of the mass of the anionic monomer, such as 0.3%, 0.4%, 0.5% or a range consisting of any two of them. The amount of the cross-linking agent added is 0.1% to 0.3% of the mass of the anionic monomer, such as 0.1%, 0.2%, 0.3% or a range consisting of any two of them.

[0056] In some embodiments, the anionic monomer includes at least one of vinyl sulfonic acid, allyl sulfonic acid, 2-acrylamide-1-methylpropane sulfonic acid, 2-acrylamide-2-methylpropane sulfonic acid, and 2-methacrylamide-2-methylpropane sulfonic acid; and / or, the initiator includes at least one of potassium persulfate, ammonium persulfate, and azobisisobutyronitrile; and / or, the cross-linking agent includes at least one of diisopropyl peroxide and benzoyl peroxide.

[0057] The third curing agent of the present invention includes a silane compound. In a specific use process, the silane compound can be first mixed with water to form a solution containing the silane compound, and then used as the third curing agent in combination with the first curing agent and the second curing agent, and then mixed with solid waste to form a solidified body. In some embodiments, the third curing agent is a solution containing a silane compound, and the mass content of the silane compound in the solution containing the silane compound is 0.5-1%, for example, 0.5%, 0.8%, 1% or a range composed of any two thereof.

[0058] Among them, the silane compound can be a bifunctional silane compound. Bifunctional silane compounds refer to organic silicon compounds containing two silicon functional groups, and the general structure can be expressed as R2SiX2, where R represents an organic group and X represents a silicon functional group. These functional groups can react with other compounds to undergo cross-linking or modification, thereby promoting the first curing agent and the second curing agent to adhere closely to the surface of the solid waste.

[0059] In some embodiments, the silane compound includes at least one of 1,2-bis(trimethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethane, 1,6-bis(trimethoxysilyl)hexane, 1,6-bis(triethoxysilyl)hexane, 1,8-bis(trimethoxysilyl)octane, and 1,8-bis(triethoxysilyl)octane. In some preferred embodiments, the silane compound includes at least one of 1,2-bis(trimethoxysilyl)ethane and 1,2-bis(triethoxysilyl)ethane.

[0060] The second aspect of the present invention provides a method for solidifying heavy metals in coal gangue, the solidification method comprising: mixing coal gangue with a solidifying agent to form a solidified body; curing the solidified body to solidify the heavy metals in the coal gangue; wherein the solidifying agent is the heavy metal solidifying agent provided in the first aspect.

[0061] In the specific implementation process of the present invention, when the third curing agent is a solution containing a silane compound, the first curing agent and the second curing agent can be added to the third curing agent, and after stirring, a heavy metal curing agent is obtained, and then the heavy metal curing agent is mixed with coal gangue to form a solidified body; the solidified body is cured to solidify the heavy metal therein.

[0062] Due to the use of the above-mentioned heavy metal solidifying agent with excellent performance, the present invention can achieve long-term solidification of heavy metals in coal gangue, reduce environmental pollution, and the formed solidified body has excellent compressive strength, can achieve long-term service, and prevent heavy metal dissolution.

[0063] In some embodiments, the mass ratio of coal gangue to heavy metal curing agent is (1-3):1; the curing temperature is 15-35°C, the humidity is above 80%, and the curing time is 7-112 days. In some preferred embodiments, the curing temperature is 20-30°C, the humidity is 90%, and the curing time is 7-56 days.

[0064] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0065] Example 1

[0066] The preparation method of the heavy metal curing agent of this embodiment comprises the following steps:

[0067] 1. Preparation of curing agent I

[0068] According to the mass fraction, 80 parts of silt, 20 parts of fly ash and 30 parts of bentonite were mixed evenly to obtain curing agent I.

[0069] 2. Preparation of curing agent II:

[0070] S1, take 100 mesh quartz sand and calcium carbonate, wash and dry them, mix the quartz sand and calcium carbonate in a mass ratio of 1:0.75, and calcine them at 300° C. for 1.5 h in a nitrogen atmosphere to obtain a quartz sand / calcium carbonate blend.

[0071] S2, ultrasonically dispersing the obtained quartz sand / calcium carbonate blend in a 6wt% urea solution, heat-stirring the mixture at 125°C for 6h, filtering the mixture after the reaction is completed, washing and drying the obtained product, and obtaining a surface hydroxylated quartz sand / calcium carbonate blend.

[0072] S3, dissolving chitosan in a hydrochloric acid solution with a concentration of 4wt%, adding 2-acrylamide-1-methylpropane sulfonic acid (the mass ratio of 2-acrylamide-1-methylpropane sulfonic acid to chitosan is 2:1) and potassium persulfate (the amount of potassium persulfate added is 0.4% of the mass of 2-acrylamide-1-methylpropane sulfonic acid), stirring and reacting at 70°C for 2h, keeping the temperature unchanged after the reaction, adding surface hydroxylated quartz sand / calcium carbonate blend (the mass ratio of surface hydroxylated quartz sand / calcium carbonate blend to chitosan is 1:1.5), stirring evenly, then cooling to room temperature, adding benzoyl peroxide (the amount of benzoyl peroxide added is 0.2% of the mass of 2-acrylamide-1-methylpropane sulfonic acid), stirring continuously for 3h, standing for 2h after the stirring, washing, drying, crushing the obtained product, and passing through a 300-mesh sieve to obtain a curing agent II.

[0073] 3. Preparation of curing agent III:

[0074] 1,2-bis(trimethoxysilyl)ethane was dissolved in water to obtain a 1,2-bis(triethoxysilyl)ethane solution having a mass content of 0.75%, namely, curing agent III.

[0075] 4. Preparation of heavy metal curing agent

[0076] According to the mass percentage, 70 parts of curing agent I, 15 parts of curing agent II and 125 parts of curing agent III were mixed to obtain the heavy metal curing agent of this embodiment.

[0077] Example 2

[0078] The preparation method of the heavy metal curing agent of this embodiment comprises the following steps:

[0079] 1. Preparation of curing agent I

[0080] According to the mass fraction, 100 parts of silt, 10 parts of fly ash and 40 parts of bentonite were mixed evenly to obtain curing agent I.

[0081] 2. Preparation of curing agent II:

[0082] S1, take 80 mesh quartz sand and calcium carbonate, wash and dry them, mix the quartz sand and calcium carbonate in a mass ratio of 1:1, and calcine them at 200° C. for 2 h in a nitrogen atmosphere to obtain a quartz sand / calcium carbonate blend.

[0083] S2: Ultrasonic dispersion of the obtained quartz sand / calcium carbonate blend in a 10 wt% sodium carbonate solution, heat stirring treatment at 150° C. for 2 h, filtering after the reaction is completed, washing and drying the obtained product to obtain a surface hydroxylated quartz sand / calcium carbonate blend.

[0084] S3, dissolving chitosan in a 5wt% hydrochloric acid solution, adding 2-acrylamide-2-methylpropane sulfonic acid (the mass ratio of 2-acrylamide-2-methylpropane sulfonic acid to chitosan is 1:1) and azobisisobutyronitrile (the amount of azobisisobutyronitrile added is 0.3% of the mass of 2-acrylamide-2-methylpropane sulfonic acid), stirring and reacting at 80°C for 1h, keeping the temperature unchanged after the reaction, adding surface hydroxylated quartz sand / calcium carbonate blend (the mass ratio of surface hydroxylated quartz sand / calcium carbonate blend to chitosan is 1:2) and stirring evenly, then cooling to room temperature, adding diisopropylbenzene peroxide (the amount of diisopropylbenzene peroxide added is 0.1% of the mass of 2-acrylamide-2-methylpropane sulfonic acid), stirring continuously for 2h, standing for 3h after the stirring, washing, drying, and crushing the obtained product, and passing through a 200-mesh sieve to obtain a curing agent II.

[0085] 3. Preparation of Curing Agent III

[0086] 1,2-bis(triethoxysilyl)ethane was dissolved in water to obtain a 1,2-bis(triethoxysilyl)ethane solution with a mass content of 1%, namely, curing agent III.

[0087] 4. Preparation of heavy metal curing agent

[0088] According to the parts by mass, 60 parts of curing agent I and 10 parts of curing agent II are added to 100 parts of curing agent III in sequence, and the mixture is stirred evenly to obtain the heavy metal curing agent of this embodiment.

[0089] Example 3

[0090] The preparation method of the heavy metal curing agent of this embodiment comprises the following steps:

[0091] 1. Preparation of curing agent I

[0092] According to the weight percentage, 60 parts of silt, 30 parts of fly ash and 20 parts of bentonite were mixed evenly to obtain curing agent I.

[0093] 2. Preparation of curing agent II:

[0094] S1, take 120 mesh quartz sand and calcium carbonate, wash and dry them, mix the quartz sand and calcium carbonate in a mass ratio of 1:0.5, and calcine them at 400° C. for 1 h in a nitrogen atmosphere to obtain a quartz sand / calcium carbonate blend.

[0095] S2, ultrasonically dispersing the obtained quartz sand / calcium carbonate blend in a 2 wt% sodium hydroxide solution, heat-stirring the mixture at 100° C. for 8 h, filtering the mixture after the reaction is completed, washing and drying the obtained product, and obtaining a surface hydroxylated quartz sand / calcium carbonate blend.

[0096] S3, dissolving chitosan in a 3wt% hydrochloric acid solution, adding 2-methacrylamide-2-methylpropane sulfonic acid (the mass ratio of 2-methacrylamide-2-methylpropane sulfonic acid to chitosan is 3:1) and potassium persulfate (the amount of potassium persulfate added is 0.5% of the mass of 2-methacrylamide-2-methylpropane sulfonic acid), stirring and reacting at 60°C for 3h, keeping the temperature unchanged after the reaction, adding surface hydroxylated quartz sand / calcium carbonate blend (the mass ratio of surface hydroxylated quartz sand / calcium carbonate blend to chitosan is 1:1) and stirring evenly, then cooling to room temperature, adding diisopropylbenzene peroxide (the amount of diisopropylbenzene peroxide added is 0.3% of the mass of 2-methacrylamide-2-methylpropane sulfonic acid), stirring continuously for 4h, standing for 1h after the stirring, washing, drying, and crushing the obtained product, and passing through a 400-mesh sieve to obtain the curing agent II.

[0097] 3. Preparation of Curing Agent III

[0098] 1,2-bis(triethoxysilyl)ethane was dissolved in water to obtain a 1,2-bis(triethoxysilyl)ethane solution with a mass content of 0.5%, thereby obtaining a curing agent III.

[0099] 4. Preparation of heavy metal curing agent

[0100] According to the parts by mass, 80 parts of curing agent I and 20 parts of curing agent II are sequentially added to 150 parts of curing agent III, and the mixture is stirred evenly to obtain the heavy metal curing agent of this embodiment.

[0101] Comparative Example 1

[0102] The difference from Example 1 is that S2 is omitted when preparing curing agent II.

[0103] Comparative Example 2

[0104] The difference from Example 1 is that when preparing curing agent II, S3 is omitted and the surface hydroxylated quartz sand / calcium carbonate blend is used as curing agent II.

[0105] Comparative Example 3

[0106] The difference from Example 1 is that no curing agent II is added.

[0107] Comparative Example 4

[0108] The difference from Example 1 is that no curing agent I is added.

[0109] Comparative Example 5

[0110] The difference from Example 1 is that the curing agent III is water.

[0111] Comparative Example 6

[0112] The difference from Example 1 is that no curing agent I and curing agent II are added.

[0113] Example 4

[0114] The difference from Example 1 is that, based on parts by mass, 70 parts of curing agent I are replaced by 40 parts of curing agent I.

[0115] Example 5

[0116] The difference from Example 1 is that, based on parts by mass, 70 parts of curing agent I are replaced by 100 parts of curing agent I.

[0117] Example 6

[0118] The difference from Example 1 is that, based on the mass fraction, 15 parts of curing agent II are replaced by 5 parts of curing agent II.

[0119] Example 7

[0120] The difference from Example 1 is that, based on parts by mass, 15 parts of curing agent II are replaced by 30 parts of curing agent II.

[0121] Example 8

[0122] The difference from Example 1 is that, based on parts by mass, 125 parts of curing agent II are replaced by 80 parts of curing agent II.

[0123] Example 9

[0124] The difference from Example 1 is that, based on parts by mass, 125 parts of curing agent II are replaced by 200 parts of curing agent II.

[0125] Test example

[0126] 1. Preparation of solidified body

[0127] Preparation of gangue / curing agent composite (cured body): according to the mass ratio of heavy metal curing agent to gangue of 1:3, the gangue is added to the heavy metal curing agent, and the mixture is stirred evenly to obtain a mixture, and the mixture is injected into a cylindrical mold (diameter 5 cm, height 10 cm) and solidified for 24 hours and then demolded. After demolding, it is moved into a standard curing box with constant temperature and humidity (curing temperature and humidity are 20°C and 90%, respectively) and cured for 7 days, 14 days, and 28 days, respectively, to obtain a gangue / curing agent composite.

[0128] 2. Compressive strength test

[0129] According to "GB / T 17671-2021-Test method for strength of cement mortar (ISO method)", the unconfined compressive strength test of coal gangue / curing agent composite was carried out. The experiment was measured using a fully automatic constant stress pressure testing machine (in accordance with JC / T 960 standard requirements), and the machine's load application rate was uniformly set to 0.1mm / min.

[0130] 3. Heavy metal curing effect detection

[0131] The curing effect test of heavy metal cadmium (according to previous studies, heavy metal cadmium is the main excessive content in gangue) of the gangue / curing agent complex is carried out according to the method in the industry standard "HJ 766-2015 Determination of Metal Elements in Solid Waste by Inductively Coupled Plasma Mass Spectrometry". The specific operation is as follows:

[0132] Using a pH = 2 mixed nitric acid and sulfuric acid solution as the leaching solution, soak the solidified gangue / curing agent complex in a barrel containing 1L of leaching solution at a fixed solid-liquid ratio of 1:10, and seal the barrel mouth. The sampling time is set to 1d, 7d, 14d, 28d, 56d, and 112d respectively. Take about 5mL of leaching solution with a syringe each time, filter it into a 10mL centrifuge tube using a 0.45μm filter membrane, and obtain the leaching solution to be tested. During the test, the same variable part is tested 3 times to calibrate the experimental error. After sampling, the immersion solution is filled to a constant volume of 1L.

[0133] The test results are shown in Table 1 and Table 2.

[0134] Table 1 Compressive strength of gangue / hardener composite

[0135]

[0136] Table 2 Heavy metal curing effect of gangue / curing agent composite

[0137]

[0138]

[0139] According to Table 1, the compressive strength of the cured bodies formed by curing with the curing agents of Comparative Examples 1 to 6 is relatively low, while the compressive strength of the cured bodies formed by curing with the curing agents of Examples 1 to 3 is significantly improved, indicating that the curing agent of the present invention can improve the compressive strength of the cured body.

[0140] According to Table 2, different curing agents have obvious differences in the curing effects of Cd in coal gangue, and within a certain time range, the Cd content in the leachate shows an upward trend with the passage of time. Compared with Comparative Examples 1 to 6, the Cd content of the solidified bodies obtained after the curing agents of Examples 1 to 3 are coated and solidified on the coal gangue increases slowly with the passage of time and the concentration is low, indicating that the heavy metal curing agent provided by the present invention has excellent long-term curing effect.

[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A heavy metal curing agent, characterized in that: The heavy metal curing agent includes: a first curing agent, a second curing agent and a third curing agent; wherein the first curing agent includes silt, fly ash and bentonite, the second curing agent includes a blend and chitosan loaded on the surface of the blend, the blend includes quartz sand and calcium carbonate, and the third curing agent includes a silane compound.

2. The heavy metal curing agent according to claim 1, characterized in that In terms of weight, the heavy metal curing agent includes: 60-80 parts of a first curing agent, 10-20 parts of a second curing agent and 100-150 parts of a third curing agent; and / or, in terms of weight, the first curing agent includes: 60-100 parts of silt, 10-30 parts of fly ash and 20-40 parts of bentonite.

3. The heavy metal curing agent according to claim 1, characterized in that In the second curing agent, the mass ratio of the blend to the chitosan is 1:(0.5-2.5), and the mass ratio of the quartz sand to the calcium carbonate is 1:(0.5-1).

4. The heavy metal curing agent according to claim 1, characterized in that The preparation method of the second curing agent comprises the following steps: S1, mixing quartz sand and calcium carbonate, and calcining them under an inert atmosphere to obtain a blend; S2, mixing the blend with an alkaline solution, and performing a first thermal stirring to hydroxylate the surface of the blend to obtain an intermediate product; S3, mixing chitosan with an acid solution to obtain a solution containing chitosan; mixing the solution containing chitosan, anionic monomer and initiator, and performing a second hot stirring to obtain a mixed solution; adding the intermediate product and cross-linking agent to the mixed solution, and performing a third stirring to obtain the second curing agent.

5. The heavy metal curing agent according to claim 4, characterized in that: The calcination temperature is 200-400°C and the calcination time is 1-2h; and / or, The first thermal stirring is performed at a temperature of 100 to 150° C., a rotation speed of 200 to 400 rpm, and a time of 2 to 8 hours; and / or, The second thermal stirring temperature is 60-80°C, the rotation speed is 200-400 rpm, and the time is 1-3 hours; and / or, The third stirring temperature is 20-30°C, the rotation speed is 200-400 rpm, and the time is 2-4 hours; and / or, After the first heat stirring, the first heat stirring product is subjected to a first washing and a first drying to obtain the intermediate product; and / or After the third stirring, the third stirring product is subjected to a second washing, a second drying, and a pulverization, and passed through a 200-400 mesh sieve to obtain the second curing agent; and / or, The mass content of the alkaline compound in the alkaline solution is 2% to 10%, and the mass content of the acidic compound in the acid solution is 3% to 5%; Preferably, the alkaline compound includes at least one of sodium hydroxide, sodium carbonate and urea; Preferably, the acidic compound includes at least one of hydrochloric acid, nitric acid and sulfuric acid.

6. The heavy metal curing agent according to claim 4, characterized in that The mass ratio of the quartz sand to the calcium carbonate is 1:(0.5-1); and / or, The mass ratio of the intermediate product to the chitosan is 1:(1-2); and / or, The mass ratio of the anionic monomer to the chitosan is (1-3):1; and / or, The amount of the initiator added is 0.3% to 0.5% of the mass of the anionic monomer; and / or, The amount of the cross-linking agent added is 0.1% to 0.3% of the mass of the anionic monomer; Preferably, the anionic monomer includes at least one of vinyl sulfonic acid, allyl sulfonic acid, 2-acrylamide-1-methylpropane sulfonic acid, 2-acrylamide-2-methylpropane sulfonic acid, and 2-methacrylamide-2-methylpropane sulfonic acid; Preferably, the initiator comprises at least one of potassium persulfate, ammonium persulfate, and azobisisobutyronitrile; Preferably, the cross-linking agent includes at least one of dicumyl peroxide and benzoyl peroxide.

7. The heavy metal curing agent according to any one of claims 1 to 6, characterized in that: The third curing agent is a solution containing a silane compound, and the mass content of the silane compound in the solution containing the silane compound is 0.5% to 1%.

8. The heavy metal curing agent according to claim 7, characterized in that The silane compound includes a bifunctional silane compound; Preferably, the silane compound includes at least one of 1,2-bis(trimethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethane, 1,6-bis(trimethoxysilyl)hexane, 1,6-bis(triethoxysilyl)hexane, 1,8-bis(trimethoxysilyl)octane and 1,8-bis(triethoxysilyl)octane; More preferably, the silane compound includes at least one of 1,2-bis(trimethoxysilyl)ethane and 1,2-bis(triethoxysilyl)ethane.

9. A method for solidifying heavy metals in coal gangue, characterized in that: The solidification method comprises: mixing coal gangue with a solidifying agent to form a solidified body; curing the solidified body to solidify the heavy metals in the coal gangue; wherein the solidifying agent is the heavy metal solidifying agent according to any one of claims 1 to 8.

10. The curing method according to claim 9, characterized in that: The mass ratio of the coal gangue to the heavy metal solidifying agent is (1-3):1; and / or, The curing temperature is 15 to 35° C., the humidity is above 80%, and the curing time is 7 to 112 days; Preferably, the curing temperature is 20-30° C., the humidity is 90%, and the curing time is 7-56 days.

Citation Information

Cited By

  • Dust heavy metal treatment system and treatment method

    CN120079681A

  • Preparation method of low-temperature humified coal gangue-agriculture and forestry solid waste porous slow-release humic acid water-soluble fertilizer

    CN120309422A